Developing listening comprehension skills in the English language classroom - Sherzod Sultanovich Samandarov (Science and Education, 2025)
Listening comprehension is one of the most fundamental yet challenging components of English language acquisition. It plays a crucial role in shaping learners’ overall communicative competence and fluency. Despite its significance, many EFL (English as a Foreign Language) learners struggle to decode spoken input due to limited exposure, lack of effective strategies, and insufficient classroom focus on listening processes. This paper explores the key factors that influence the development of listening comprehension in EFL contexts, emphasizing pedagogical approaches, cognitive and affective variables, and the integration of authentic materials. Drawing on recent theoretical and empirical studies, the article argues that effective listening instruction requires a combination of metacognitive strategy training, exposure to real-life input, and interactive classroom practices. The findings highlight the importance of teacher awareness, learner autonomy, and technology-enhanced learning environments in promoting sustained listening improvement.